An assessment of the efficacy of a rotary and a reciprocating retreatment file system for removal of gutta-percha from root canals: An in vitro cone-beam computed tomography study - Kapil Dasaram Wahane; Shraddha Shekhar Kulkarni; Sadashiv Daokar; Kalpana Patil; Karishma Patel; Trupti Thorat (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this study was to compare the NeoEndo and WaveOne retreatment systems concerning the effective removal of epoxy resin-based sealer and gutta-percha during the retreatment of straight root canals. Materials and Method: Sixty extracted, human mandibular first premolars with single straight roots were selected based on cone-beam computed tomography (CBCT) evaluations. The root canals were instrumented with the ProTaper system up to the F3 file and filled with gutta-percha and epoxy resin-based sealer using the cold lateral condensation technique. After 1 month, the samples were randomly divided into two groups (n = 30) according to the retreatment system used: NeoEndo and WaveOne. A CBCT device scanned specimen after the root filling and retreatment procedures, and the decrease in the volume of filling material after each retreatment protocol was measured. The results were analyzed using the paired t-test and additional box-and-whisker plots. Results: The WaveOne removed significantly more material than the NeoEndo (P = 0.005) system. Conclusion: The WaveOne system was more effective than the NeoEndo retreatment system during the removal of filling material.